If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3u + 7) = 4(3 + -2u) Reorder the terms: 2(7 + 3u) = 4(3 + -2u) (7 * 2 + 3u * 2) = 4(3 + -2u) (14 + 6u) = 4(3 + -2u) 14 + 6u = (3 * 4 + -2u * 4) 14 + 6u = (12 + -8u) Solving 14 + 6u = 12 + -8u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '8u' to each side of the equation. 14 + 6u + 8u = 12 + -8u + 8u Combine like terms: 6u + 8u = 14u 14 + 14u = 12 + -8u + 8u Combine like terms: -8u + 8u = 0 14 + 14u = 12 + 0 14 + 14u = 12 Add '-14' to each side of the equation. 14 + -14 + 14u = 12 + -14 Combine like terms: 14 + -14 = 0 0 + 14u = 12 + -14 14u = 12 + -14 Combine like terms: 12 + -14 = -2 14u = -2 Divide each side by '14'. u = -0.1428571429 Simplifying u = -0.1428571429
| I=-217453+109x | | I=109x-217453 | | -3x+14=2 | | 10x+5=12x-1 | | 4a+6=30 | | 4a+6=35 | | 4x+2=6-2 | | 8(3x-9)=4(6x+6) | | 6x-3=39 | | 12a+24=48 | | 3(5z-1)-3(z+7)=7(z+1) | | X*17=-13 | | 9-3(-8)+4= | | -4(2-y)+3y=3(y-4) | | -94.8+b-43.161=-168.05 | | 6x-(2x+3)=1 | | 5.9x+3.5=15.3 | | 5.9+3.5=15.3 | | 9x-28=2x | | -8-n=-3(2n-4) | | 4x+1=(x-16) | | 38+7+7q=59 | | 2X+11Y=13 | | N=20M | | n-11-32=-95 | | -2(X+3)=-5X-9 | | 1x=4 | | -30=5(Y-3)-8Y | | 7x+7x= | | -5=3W+4 | | 2V+17=49 | | 3(x+6)=48 |